The design of Visual Support Educational Games Dental and Oral Health - Desy Nur Fitriana; T. Brenda Chandrawati (SISFORMA, 2015)
Game is one of the e-learning are quite popular among children, because in our educational games not only play games but also we can learn something new. Knowledge of oral health education is packaged in an educational game in the visual depiction good with children will better understand the purpose of delivering education that can be applied in everyday life. And in this paper will discuss game design visualization in dental and oral health education so that children can be in demand in the form of a game gadget or smartphone.